الأسعار العالمية للغاز الطبيعي ومستقبلها - بن أحمد, أحمد (جامعة الوادي University of Eloued, 2016)
ظل تسعير الغاز الطبيعي مرتبطا بتسعير النفط، وظلت ومازالت الدول المصدرة للغاز تطالب بفك هذا الارتباط على أن يكون للغاز سوقا منفصلة عن السوق العالمية للنفط، وكان من نتائج هذا الارتباط أن انخفاض أسعار النفط في القرن 90 كان له تأثير سلبي على أسعار الغاز رغم ما يتكلفه إنتاج الغاز من استثمارات باهظة. وقد ناقشت الدول المنتجة والمصدرة للغاز الطبيعي ربط سعر الغاز بسعر النفط في المؤتمرات والاجتماعات الخاصة بالنفط والغاز، والتي كانت تعقد في العديد من الدول: مثل مؤتمر الغاز المنعقد بالإمارات سنة 1996، ومؤتمر الشرق الأوسط للغاز والنفط بألو ظبي والتي نادت بضرورة تكوين رابطة لمنتجي الغاز على غرار منظمة الأوبك، تظم معظم الدول الكبرى المنتجة والمصدرة للغاز مثل: روسيا، إيران، قطر، الإمارات، الجزائر، ماليزيا، اندونيسيا وغيرها لتنسيق التعاون في مسألة تسعير الغاز وصناعته. كما ناقشت الجزائر خلال المنتدى العاشر للدول المصدرة للغاز والذي أنعقد في سنة 2009 بوهران مسألة تسعير الغاز، وأكدت على ضرورة مراجعة أسعار الغاز في الأسواق العالمية لإيجاد سعر عادل من خلال اللجوء إلى الاتفاق بخصوص تخفيض الإنتاج، لإيجاد آليات تضمن سعرا حقيقيا للغاز. The indexing of natural gas remained tied with the price of oil, the exporting countries of the gas suggests and denounces this dependency, for that the gas market has become independent of the oil market , among the consequences of this dependence in the years 90 , is when the price of oil will fall automatically , the price of gas also changes , despite the fact that the gas production costs of investments it's expensive. The Exporters of the gases have discussed long this dependence in the congresses and seminars such as in the UAE 1996 and in the Middle East Congress of the gas and oil in Abu Dhabi or the participants called for the requirement to base a league producers of gas outside of OPEC ,which brings together the countries such : Russia ,Iran ,Qatar ,UAE ,Algeria ,Malaysia, Indonesia ...etc. to coordinate cooperation concerning the indexation of gas and its industry. As well in the 10 th Forum of the exporting countries of the gas to Oran in 2009, or the recommendations was the need for the revision of the price of gas in the global markets in order to arrive at a fair price with a consensus of decrease of production , and to find mechanisms that ensure a real gas price.
World prices of natural gas and its future
مقال- مجلة رؤى اقتصادية
Keywords: الغاز الطبيعي، أسعار الغاز الطبيعي، الطاقة .; natural gas, and natural gas prices, energy